2003
DOI: 10.1124/jpet.103.049395
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of (2S,4Z)-N-[(2S)-2-Hydroxy-2-phenylethyl]-4-(methoxyimino) -1-[(2′-methyl[1,1′-biphenyl]-4-yl)carbonyl]-2-pyrrolidinecarboxamide, a New Potent and Selective Nonpeptide Antagonist of the Oxytocin Receptor

Abstract: We have discovered a new, potent, selective, and orally active oxytocin receptor antagonist, (2S,4Z)-N-[(2S)-2-hydroxy-2-phenylethyl]-4-(methoxyimino)-1-[(2Ј-methyl[1,1Ј-biphenyl]-4-yl)carbonyl]-2-pyrrolidinecarboxamide (compound 1).We report the biochemical, pharmacological, and pharmacokinetic characterization in vitro and in vivo of this compound. Premature birth is a major problem in obstetrics affecting about 10% of all births and being the largest cause of perinatal morbidity and mortality. The impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 23 publications
2
39
1
1
Order By: Relevance
“…It was equipotent at rat OT and V2 receptors and 10-fold selective for rat OT vs. rat V1 receptors ( Table 1). The selectivity of atosiban was very similar to that reported in the literature by various groups (6,20,36). For example, Cirillo et al (6) found that atosiban was 23-fold more potent at hV1a than hOT and only 8 and 12-fold more potent at hOT than V1b and V2, respectively.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…It was equipotent at rat OT and V2 receptors and 10-fold selective for rat OT vs. rat V1 receptors ( Table 1). The selectivity of atosiban was very similar to that reported in the literature by various groups (6,20,36). For example, Cirillo et al (6) found that atosiban was 23-fold more potent at hV1a than hOT and only 8 and 12-fold more potent at hOT than V1b and V2, respectively.…”
Section: Resultssupporting
confidence: 71%
“…Recently discovered nonpeptide antagonists are reported to have much better selectivity for OTR vs. V1aR; however, none approach the selectivity of GSK221149A. For example, the compounds described by Cirillo et al (6), Serradeil-Le Gal et al (31) (SSR126768A), and Bell et al (2) (L-372,662) are 6-, 95-, and 609-fold selective for hOTR vs. hV1aR, while GSK221149A is Ͼ18,000-fold selective. In addition, GSK221149A (1,500-fold) is much more selective than SSR126768A (62-fold) at rat OTR vs. rat V1a (data for the other two previously mentioned nonpeptide antagonists are lacking).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This captures the overall effect on contraction work rate including intensity, frequency and length of single contractions (Cirillo et al, 2003(Cirillo et al, , 2007. Both OBE022, given orally, and OBE002, administered i.v., reduced markedly and dose-dependently the spontaneous uterine contractions in late-term pregnant rats at gestational days (GD) 19-21 ( Figure 6).…”
Section: Inhibition Of Spontaneous Uterine Contractions In the Pregnamentioning
confidence: 99%
“…Experimental conditions described by Cirillo et al, 2003Cirillo et al, , 2007 For the oral administration the same computation procedure was applied at different time points after treatment.…”
Section: Spontaneous Uterine Contractions In Anesthetized Late-term Pmentioning
confidence: 99%